1988
DOI: 10.2165/00003088-198814030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Oral Buspirone in Patients with Impaired Renal Function

Abstract: 12 patients with mild to moderate impairment of renal function and 12 healthy subjects each received 20mg buspirone as a single dose in this acute study. Six anuric patients with chronic renal failure were given two 20mg doses of buspirone, the first 2 days before haemodialysis (between dialyses) and the second during hemodialysis (2 hours before dialysis began). The differences between the median pharmacokinetic values of buspirone for healthy subjects, patients with mild to moderate renal impairment, and anu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Single-dose pharmacokinetics of buspirone have been investigated in patients with renal [6] or hepatic [7] impairment. The study in patients with renal failure [6] indicated that the apparent clearance ofbuspirone and 1-PP in anuric patients was approximately one-third of that in normal subjects, and that there was no significant relationship between creatinine clearance and apparent buspirone clearance. The single-dose and steady-state pharmacokinetic data from the present study confirmed that the disposition of buspirone was not related to the degree of renal impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Single-dose pharmacokinetics of buspirone have been investigated in patients with renal [6] or hepatic [7] impairment. The study in patients with renal failure [6] indicated that the apparent clearance ofbuspirone and 1-PP in anuric patients was approximately one-third of that in normal subjects, and that there was no significant relationship between creatinine clearance and apparent buspirone clearance. The single-dose and steady-state pharmacokinetic data from the present study confirmed that the disposition of buspirone was not related to the degree of renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Buspirone clearance in patients with renal impairment was approximately a third to a half of that in normal volunteers [6]. However, in a single-dose pharmacokinetic study in patients with hepatic impairment, a 16-fold increase in plasma level and a significant increase in the half-life of buspirone were reported in cirrhotic patients compared to healthy subjects [7].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…More specifically, successful buspirone use has been reported in two case studies of dementia patients with disruptive behaviors (Tiller et al, 1988;Colenda, 1988). In addition, buspirone offers several advantages over neuroleptics and benzodiazepines for use in the elderly, including the absence of adverse effect on motor performance and cognitive function, an advantageous side-effect profile, and predictable pharmacokinetics and metabolism (Newton et al, 1982;Smiley and Moskowitz, 1986;Newton et af., 1986;Hart et af., 1991;Lucki et al, 1987;Robinson et al, 1988;Bohm et al, 1990;Gammans et al, 1989;Caccia et al, 1988).…”
mentioning
confidence: 99%
“…Buspirone is extensively metabolized by the liver to various metabolites including 1‐prymidinyl‐piperazine (1‐PP), which has approximately 1/20th the anxiolytic activity of buspirone. 1‐PP AUC and half‐life were significantly higher in anuric HD patients compared to healthy controls . Although HD significantly reduced 1‐PP AUC, 1‐PP AUC was still greater than in healthy subjects.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 80%